The association of cultural and environmental factors with mental health among Asian immigrants. Issue 4 (30th August 2021) - Kim, Jaehyun; Mowen, Andrew; Hickerson, Benjamin; Graefe, Alan; Bopp, Melissa
Abstract : Purpose: During exposure to new cultures, immigrants face numerous life changes and challenges, which negatively affect mental health, yet environmental supports may address these concerns. This study aims to examine how neighborhood quality, acculturation and acculturative stress are associated with immigrants' mental health. Design/methodology/approach: The sample consisted of 511 Asian immigrants who were born in their country of origin and immigrated to the USA. Path analysis using analysis of moment structures (version 22.0) was conducted to test the hypothesized model. Findings: The results from the path analysis indicated that perceived neighborhood quality and acculturative stress had direct effects on mental health among Asian immigrants. The study also found a significant indirect pathway to mental health where more favorable perceptions of neighborhood quality were associated with higher levels of acculturation and lower levels of acculturative stress, which, in turn, resulted in better mental health. Originality/value: The results of the study highlight the importance of improving neighborhood quality as a means by which to facilitate cultural adjustment/adaptation to US culture and thus, improve mental health among Asian immigrants. In addition, the authors suggested considering cultural origin in designing health programs and/or policies for Asian immigrants, which could promote mental health among Asian immigrants. Based on the results of the model, this study produced insightful information and suggestions on how to improve Asian immigrants' mental health more effectively.